2001
DOI: 10.2165/00129785-200101020-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Analysis of Gene Expression and Variability in Gene Arrays Based on Repeated Observations

Abstract: These findings have implications relating to the use of gene arrays to detect variance of gene expression, and should be taken into consideration in the prospective design of array experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Evaluation for longer periods of time show a reentry into cell attachment, but of lower magnitude than observed with the first cycle (unpublished observations). Prior gene array-based studies indicated that endoglin expression increased during cell detachment (Jovanovic et al, 2001). However, array findings were never confirmed by Northern blot.…”
Section: Endoglin Is Down-regulated During Prostate Cell Detachmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Evaluation for longer periods of time show a reentry into cell attachment, but of lower magnitude than observed with the first cycle (unpublished observations). Prior gene array-based studies indicated that endoglin expression increased during cell detachment (Jovanovic et al, 2001). However, array findings were never confirmed by Northern blot.…”
Section: Endoglin Is Down-regulated During Prostate Cell Detachmentmentioning
confidence: 96%
“…We found that metastatic variant PC3-M cells exhibited a unique pattern of cell adhesion, characterized by rapid attachment, followed by detachment. Focusing upon genes important in regulating cell detachment, we developed a novel statistical approach wherein multiple replicates of gene array experiments were used to calculate mean and variance of gene expression, for all genes (Jovanovic et al, 2001;. In this manner, genes whose expression was significantly up-or downregulated, as compared to that associated with normal gene variance, could be identified, and investigated further.…”
Section: Introductionmentioning
confidence: 99%
“…The metastatic behavior of cells is heavily dependent upon the cellular functions of migration and invasion (Poste and Fidler, 1980;Bissell and Radisky, 2001). Using gene arrays to identify regulators of PCa cell motility, we uniquely identified endoglin (ENG) (Jovanovic et al, 2001). ENG is a 180 kDa homodimeric type I transmembrane transforming growth factor b (TGFb) binding protein (Cheifetz et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described similar findings before in studies involving only nonamplified (i.e., native) RNA. 22 Most importantly, when LCM was coupled to linear amplification and array data pooled across different subjects, genes were found to be differentially expressed when normal epithelial cells were compared to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In studies using only non-amplified (or native) RNA, we have previously reported that there is increased variability in gene expression profiles when comparing RNA from different, as apposed to identical RNA batches. 22 Data in Figure 3a were generated from the same batch of RNA, for each cell line tested. To further characterize sources of variability, RNA was isolated from PC3 and PC3-M cells at two separate times, aRNA generated, and aPC3/aPC3-M versus PC3/PC3-M determined, for non-trivial genes ( Figure 4).…”
Section: Evaluating Other Factors: Variability In Gene Expressionmentioning
confidence: 99%